Translation elicits a growth rate‐dependent, genome‐wide, differential protein production in Bacillus subtilis. Issue 5 (18th May 2016) - Borkowski, Olivier; Goelzer, Anne; Schaffer, Marc; Calabre, Magali; Mäder, Ulrike; Aymerich, Stéphane; Jules, Matthieu; Fromion, Vincent
Abstract: Complex regulatory programs control cell adaptation to environmental changes by setting condition‐specific proteomes. In balanced growth, bacterial protein abundances depend on the dilution rate, transcript abundances and transcript‐specific translation efficiencies. We revisited the current theory claiming the invariance of bacterial translation efficiency. By integrating genome‐wide transcriptome datasets and datasets from a library of synthetic gfp ‐reporter fusions, we demonstrated that translation efficiencies in Bacillus subtilis decreased up to fourfold from slow to fast growth. The translation initiation regions elicited a growth rate‐dependent, differential production of proteins without regulators, hence revealing a unique, hard‐coded, growth rate‐dependent mode of regulation. We combined model‐based data analyses of transcript and protein abundances genome‐wide and revealed that this global regulation is extensively used in B. subtilis . We eventually developed a knowledge‐based, three‐step translation initiation model, experimentally challenged the model predictions and proposed that a growth rate‐dependent drop in free ribosome abundance accounted for the differential protein production. Synopsis: Genome‐wide transcriptome and proteome data, measurements of translation efficiency in a library of synthetic reporter fusions and a mathematical model of protein production show that translation efficiency is growth rate dependent and transcript specific. The gene‐specific translation initiation region (TIR) drives a growth‐dependent, differential production of proteins in the absence of regulators. Bacterial translation efficiency drops with increasing growth rate and is well represented by a Michaelis–Menten‐type rate law as a function of free ribosomes. The mathematical model of protein production was challenged with transcriptome and proteome data and revealed a large repertoire of differentially translated transcripts as a function of the growth rate. Abstract : Genome‐wide transcriptome and proteome data, measurements of translation efficiency in a library of synthetic reporter fusions and a mathematical model of protein production show that translation efficiency is growth rate dependent and transcript specific.